2022
DOI: 10.1007/s11356-022-24396-5
|View full text |Cite
|
Sign up to set email alerts
|

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China

Abstract: We aim to explore the link between maternal weekly temperature exposure and CHD in offspring and identify the relative contributions from heat and cold and from moderate and extreme atmospheric temperature. From January 2019 to December 2020, newborns who were diagnosed with CHD by echocardiography in the Network Platform for Congenital Heart Disease (NPCHD) from 11 cities in eastern China were enrolled in the present study. We appraised the exposure lag response relationship between temperature and CHDs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…This is the primary risk to developing embryos and babies [ [60] , [61] , [62] , [63] ]. Animal research using both non-ultrasound and ultrasound technologies has shown that maternal heat exposure is hazardous to the developing embryo/fetus [ 60 , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. It seems to be the case if the temperature increases by more than 1.5 °C over the physiological threshold.…”
Section: Methodsmentioning
confidence: 99%
“…This is the primary risk to developing embryos and babies [ [60] , [61] , [62] , [63] ]. Animal research using both non-ultrasound and ultrasound technologies has shown that maternal heat exposure is hazardous to the developing embryo/fetus [ 60 , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. It seems to be the case if the temperature increases by more than 1.5 °C over the physiological threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that cold environments can impact maternal blood viscosity and nutrient distribution, potentially leading to an increased occurrence of fetal growth defects. , A study based on the New York State Congenital Anomalies Registry found an association between ECEs and hypoplastic left heart syndrome and aortic stenosis . A Chinese study found minimal effects of extreme cold temperatures on neonatal prevalence, possibly as a result of the fact that the study assessed average weekly temperatures rather than ECEs . In addition, other studies have found an effect of ECEs on adverse pregnancy outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…24 A Chinese study found minimal effects of extreme cold temperatures on neonatal prevalence, possibly as a result of the fact that the study assessed average weekly temperatures rather than ECEs. 15 In addition, other studies have found an effect of ECEs on adverse pregnancy outcomes. 22 Thus, given the rapidly increasing frequency of extreme temperature events and the uncertainty of the results, there is a need to further investigate the impact of maternal exposure to ECEs during the critical period of organogenesis (3−8 weeks of gestation) on the pathogenesis of CHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation